2016
DOI: 10.1097/md.0000000000003090
|View full text |Cite
|
Sign up to set email alerts
|

Relative frequency, Possible Risk Factors, Viral Codetection Rates, and Seasonality of Respiratory Syncytial Virus Among Children With Lower Respiratory Tract Infection in Northeastern Brazil

Abstract: Few studies, each limited to a single major city, have investigated the prevalence and seasonal patterns of different viruses among children with low respiratory tract infections (LRTI) in Northeastern Brazil. The aim of this study was to determine the frequency of respiratory syncytial virus (RSV) and of 7 other viruses in children for LRTI in 4 capitals from this region, and investigate their association with several risk factors, including meteorological data.From April 2012 to March 2013, 507 children, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 35 publications
3
29
0
2
Order By: Relevance
“…In temperate climates, RSV detection rates were positively associated with relative humidity . However, some studies undertaken in tropical and subtropical areas have found a positive association with relative humidity, while others have found a negative association . Based on the LASSO model, we found that the RSV detection rate was higher when average relative humidity was low.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…In temperate climates, RSV detection rates were positively associated with relative humidity . However, some studies undertaken in tropical and subtropical areas have found a positive association with relative humidity, while others have found a negative association . Based on the LASSO model, we found that the RSV detection rate was higher when average relative humidity was low.…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies have shown that temperature is the meteorological factor most commonly associated with respiratory viral infections. Several studies have reported that RSV epidemics have been found to be strongly associated with changes in temperature . The incidence of RSV infection has been reported to decrease as the average temperature increases .…”
Section: Discussionmentioning
confidence: 99%
“…Because the 2019-nCoV is a sudden infectious disease, time series analysis cannot be considered (Gurgel et al, 2016;Yusef et al, 2007).…”
Section: Regression Analysis Of Incremental Cases and Meteorological mentioning
confidence: 99%
“…Previous studies have found that, in tropical, subtropical and temperate regions, RSV infections are related to meteorological factors such as temperature, RH, atmospheric pressure and rainfall Darniot et al,2018;Gurgel et al, 2016;Tian et al,2017;Sirimi et al,2016;Liu et al,2016;Chen et al,2014;du Prel et al,2009). The increase of RSV cases is negatively correlated with RH (Gurgel et al, 2016;Tian et al, 2017;Liu et al, 2016). Similarly, due to the high incidence rate of influenza virus, it brings heavy medical burden and has been fully studied.…”
Section: Relationship Between Covid-19 Epidemic and Climate Charactermentioning
confidence: 99%
See 1 more Smart Citation